Pancytopenia: etiologies and manifestation in eastern India - Singh, Vikram; Singh, Mridu; Shankar Singh, Prem (International Journal of Research in Medical Sciences, 2017)
Background: Pancytopenia is the simultaneous presence of anemia, leucopenia and thrombocytopenia. The aetiologies causing pancytopenia varies depending upon factors e.g. age, sex, occupation, and geographical distribution. Unfortunately, the major treatises of haematology give more emphasis to Aplastic anaemia; while Megaloblastic anaemia is more common in developing countries than western world. Therefore, this Observational study was carried out over a period of two years in the Department of Medicine of Institute of Medical Sciences (IMS), BHU with the aim to identify etiologies of pancytopenia and its manifestation in eastern India. Methods: All the patients with features of anemia, thrombocytopenia or leukopenia were screened for pancytopenia and a total 214 cases were selected. A detailed physical examination, hematological and biochemical investigation was done. Results: The most common cause of pancytopenia in our study was Aplastic anemic (36.9%) followed by Megaloblastic anaemia (18.7%), Kala-azar (11.7%) and Myelodysplastic syndrome (10.5%). Conclusions: Megaloblastic anemia should be considered as important cause of Pancytopenia, especially when serum LDH level of patient is raised.